2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090406
|View full text |Cite
|
Sign up to set email alerts
|

Eye-screen distance monitoring for computer use

Abstract: The extended period many people now spend looking at computer screens is thought to affect eyesight over the long term. In this paper we are concerned with developing and initial evaluation of a wireless camera-based tracking system providing quantitative assessment of computer screen interaction. The system utilizes a stereo camera system and wireless XBee based infrared markers and enables unobtrusive monitoring. Preliminary results indicate that the system is an excellent method of monitoring eye-screen dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…In effect, interactive tasks (text completion, web searching and game) were associated with shorter viewing distances than the non-interactive video watching task. However, in disagreement with previous research, 19 in which no details on the study sample are provided, no statistically significant difference was found between the text completion and the web browsing tasks. It may be noted that previous research has documented a relationship between the type of task being conducted by computer operators and aspects such as eyeblink 28 rate and visual stress or fatigue.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…In effect, interactive tasks (text completion, web searching and game) were associated with shorter viewing distances than the non-interactive video watching task. However, in disagreement with previous research, 19 in which no details on the study sample are provided, no statistically significant difference was found between the text completion and the web browsing tasks. It may be noted that previous research has documented a relationship between the type of task being conducted by computer operators and aspects such as eyeblink 28 rate and visual stress or fatigue.…”
Section: Discussioncontrasting
confidence: 97%
“…The main objective of the present study was to develop an affordable (price of each sensor is about 10$), non-intrusive method to evaluate viewing distance of VDT users and to test it on a sample of participants undertaking four typical computer tasks. Previous efforts at assessing viewing distance in real time in computer users rely on either infrared 19 or ultrasound complex systems, requiring part of the equipment, or at least some markers, to be placed on the forehead of the participants. Therefore, it is believed that these approaches lack operability in that they involve non-trivial installation and configuration, and may interfere with the task being conducted by the participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations